2019
DOI: 10.1088/2631-8695/ab504f
|View full text |Cite
|
Sign up to set email alerts
|

Influence of in-service thermal softening on wear and plastic deformation in remanufactured hot forging dies

Abstract: The need for economic and greener production methods necessitates remanufacturing of used hot forging dies. However, it has been reported from industries that the remanufactured forging dies show higher wear rate, and plastic deformation as compared to new dies. In this work wear and plastic deformation behaviour in new, and remanufactured hot forging dies at different stages of forging cycles are experimentally studied. Die geometry was digitised using three dimensional optical scanner to analyse the wear dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…From figure 11, it can be observed that the optimum hardness and impact energy can be obtained in samples annealed within 940 °C and 980 °C. These observations are similar to the studies conducted in previous research [9]. After this optimum range of temperature, the hardness drops significantly.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…From figure 11, it can be observed that the optimum hardness and impact energy can be obtained in samples annealed within 940 °C and 980 °C. These observations are similar to the studies conducted in previous research [9]. After this optimum range of temperature, the hardness drops significantly.…”
Section: Resultssupporting
confidence: 92%
“…This helps to stabilize the temperature inside the specimen and prevents thermal shocks. Such thermal shocks can produce internal cracks inside the specimens [9] which will reduce the strength of such specimens. Further, the specimens were heated to austenitising temperature of 900 °C, 940 °C, 980 °C and 1020 °C, and these were furnace cooled to obtain full-annealed ferritic-pearlitic microstructure [8].…”
Section: Annealingmentioning
confidence: 99%
“…The loss of strength of the material in the tool surface layer is caused by the thermal loads and results in wear. During forging, peak temperatures in the thermally highly stressed tool areas exceed the tempering temperature of the tool material, thus softening the tool surface layer [3].…”
Section: Introductionmentioning
confidence: 99%
“…Cyclical processes with high rates in the temperature changes act during die forging simultaneously with high forces. They promote several wear mechanisms such as abrasive and/or adhesive wear, plastic deformation and tribochemical reactions [2]. In addition, crack formation and propagation are observed on the tool surface [3].…”
Section: Introductionmentioning
confidence: 99%